AFGHAN RULE IN KASHMIR (1752–1819): A CULTURAL CROSSROADS - Shabir Ahmad Lone; Kulatunga Mudiyanselage Rohitha Dasanayaka (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Kashmir, often referred to as the "Kingdom of Fairies" and "Heaven on Earth," has a rich and diverse history marked by the rule of multiple dynasties, including those of Muslim, Hindu, and Buddhist rulers. Each ruling dynasty contributed to the region’s distinct cultural heritage, shaping its identity over time. Culture, which encompasses the way of life of a community, reflects the unique characteristics of its people. The Afghan rule in Kashmir (1752–1819) was deeply rooted in Islamic principles and traditions, significantly influencing Kashmiri society. This study aims to examine the cultural values of the Afghans and their impact on Kashmiri society during this period. Historical evidence suggests that Kashmiri society underwent notable cultural and social transformations under Afghan governance. Various aspects of Kashmiri life, including social structure, customs, early marriage traditions, the status of women, language and literature, culinary practices, currency issuance, archaeological artifacts, monuments, architecture, recreational activities, theaters, the flourishing shawl industry, and the taxation system, were either directly or indirectly influenced by Afghan rule. Despite these changes, Kashmir remained a land of peace and cultural openness, embracing diverse influences and developments. This study is based on information gathered from secondary sources to analyze the cultural and social impact of Afghan rule on Kashmir.